Relationship between Serum p-Tau Levels and Impaired Cognitive Function in Type 2 Diabetes Mellitus - Riandini, Isnu Lucky; Yuliarni Syafrita; Restu Susanti; Syarif Indra; Lydia Susanti; Fanny Adhy Putri; Reno Bestari (HM Publisher, 2024)
Background: Type 2 diabetes mellitus (Type 2 DM) is a metabolic disease that causes a global crisis that threatens health and the world economy. Impaired cognitive function is a key factor in reducing health-related quality of life in type 2 DM patients. Phosphorylated Tau (p-Tau) is a microtubule protein that functions in cell signaling, synaptic plasticity, and regulation of genome stability. A malfunction of p-Tau will cause disruption of cell signaling, which can result in impaired cognitive function. This study aims to assess the relationship between serum p-Tau levels and impaired cognitive function in type 2 diabetes mellitus patients. Methods: This research is an observational study, comparative analysis with a cross-sectional design with a sample of 60 type 2 diabetes mellitus patients who sought treatment at the endocrine polyclinic at Dr. M. Djamil General Hospital Padang. Cognitive function was assessed using MoCa-Ina. Serum p-Tau levels were measured using the ELISA method. Data analysis was carried out using SPSS. Results: The average serum p-Tau level in type 2 diabetes mellitus patients with impaired cognitive function was 542.9 pg/ml. The cut-off point for serum p-Tau levels which is associated with impaired cognitive function in type 2 diabetes mellitus patients is 517.2 pg/ml. There was a significant relationship between serum p-Tau levels and impaired cognitive function in type 2 diabetes mellitus patients (p=0.039). Conclusion: There is a significant relationship between serum p-Tau levels and impaired cognitive function in type 2 diabetes mellitus patients.